O bodo de salvaterra do extremo: saberes e rituais - Teixeira, Vasco A. Valadares (Trabalhos de Antropologia e Etnologia, 2020)
The Bodo – a ritualized distribution of food – de Nossa Senhora da Consolação (of Our Lady of Consolation) is grounded in longstanding memories being ritualized with the clothing of present times. Ancestral knowledge and old eating habits root the present religious and laic practices. Today local heritage, both tangible and intangible, is consolidated, even though Festeiros and Bodeiros from the old communal organization no longer have a role. Church still persists in the sacralization of this ritualized gift of food while the – laic – local government pay the expenses. The Confraria (Confraternity) do Bodo de Salvaterra do Extremo (a village in central-eastern Portugal) assures all the organization aiming to reinforce local prestige and identity. Locals hope that future will bring both tourists and modernity to Salvaterra.